Effect of delignification and treatment of fermentation on bioetanol percent levels from coconut fabrics - Rahman Sayuti, Abdul; Rahmati, Riesta; Agustania, Shinta; Herawati, Netty; Ahmad Roni, Kiagus (International Journal of Engineering and Technology, 2019)
Indonesia's dependence on fossil fuels continues to increase, so the government strives to develop alternative energy to reduce dependence on fuel oil. Bioethanol is an alternative energy that is renewable. The production of bioethanol from coconut fiber waste is very potential because this waste is found and underutilized. Making bioethanol uses a fermentation process with Saccharomyces cerevisiae. The effect of delignification and fermentation treatment affects the density, refractive index and bioethanol content. Delignification was carried out using variations of NaOH and KOH while the fermentation treatment was in a variety of time, temperature and nutrition, the time variation lasted for 2 days, 3 days, 4 days, 5 days and 6 days, temperature variations took place at 28 ° C, 29 ° C, 30 ° C, 31 ° C and 32 ° C and variations in nutrition by using Diammonium phosphate and urea as much as 1gr, 1.5 gr, 2 gr, 2.5 gr, 3 gr. This research is expected to provide a reference for the development of alternative energy from plants.